2012
DOI: 10.9726/kspse.2012.16.3.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fuel Injection Timing on Combustion Characteristics of Biodiesel Blend Oil in Diesel Engine

Abstract: Abstract:Recently we have a growing interest in environmental pollution and alternative energy. Diesel engine is generally used to produce the power on the ground and the sea. However, the combustion characteristics are changed on account of the wear of fuel system and the altered ambient condition of the combustion chamber by the increment of the engine operation hour. Therefore combustion characteristics on fuel injection timing are experimentally investigated to find out the optimum fuel injection timing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In comparison, biodiesel oil B20 caused an average decrease of 2%. Lim et al [14] experimentally investigated the combustion properties to the timing of the fuel injection, to specify the optimum fuel injection time for an engine speed of 1800 rpm when using a mixture of biodiesel oil and diesel. A 20-year-old diesel engine was used for the study, and they reported that the maximum heat generation rate at BTDC = 24 • C was 6.77% higher than that at BTDC = 22 • C, 24.25% higher than that at BTDC = 26 • C, and 31.13% higher than that at BTDC = 28 • C. Sanli et al [15] investigated the potential usage of methane and hydrogen-enriched methane in a turbocharged common rail direct injection diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, biodiesel oil B20 caused an average decrease of 2%. Lim et al [14] experimentally investigated the combustion properties to the timing of the fuel injection, to specify the optimum fuel injection time for an engine speed of 1800 rpm when using a mixture of biodiesel oil and diesel. A 20-year-old diesel engine was used for the study, and they reported that the maximum heat generation rate at BTDC = 24 • C was 6.77% higher than that at BTDC = 22 • C, 24.25% higher than that at BTDC = 26 • C, and 31.13% higher than that at BTDC = 28 • C. Sanli et al [15] investigated the potential usage of methane and hydrogen-enriched methane in a turbocharged common rail direct injection diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…The study on the combustion and the emission characteristics according to the application of jatropha biodiesel has been conducted (Ganapathy, et al, 2011), and the study on the emission characteristics has been conducted by changing the fuel injection timing and the mode of combustion chamber (Jaichandar, et al, 2011). In addition, the study on the combustion and the emission characteristics after spraying has been conducted by applying the fuel for biodiesel to the common-rail diesel engine (Jeong, et al, 2011), and the study on the combustion characteristics according to control of the fuel injection timing has been conducted by applying the biodiesel to existing diesel engine (Lim and Cho, 2012). The desirable complete combustion in the engine means the combustion making in the form that the reactant does not occur the oxidation any more, so the improvement of atomization of the injection fuel applying the high-pressure injection is important.…”
Section: Introductionmentioning
confidence: 99%